Conservation studies of the ruins of the Gothic Kazimierz castle (2nd half of the 14th century) in Koło (Gozdów) - Niemcewicz, Piotr; Polak, Katarzyna; Gralińska-Grubecka, Aleksandra; Witkowska, Karolina; Bartz, Wojciech; Chylińska, Marta; Podgórski, Andrzej (Badania konserwatorskie ruin gotyckiego zamku kazimierzowskiego (2. poł. XIV w.) w Kole (Gozdów), 2022)
The purpose of this article is to present the conservation research carried out as part of the revitalization project of the ruins of the castle in Koło. Basis of the recognition of the monument’s construction technique, identification and determination of the properties of historical and contemporary materials, assessment of the state of preservation and analysis of destructive factors developed a program of conservation works. Research was carried out considering the findings of architectural research. Laboratory tests of the collected material were carried out by a wide team of employees using specialized research techniques. Their results are presented in this article and include petrographic, chemical and thermogravimetric analyses of mortars, rocks and bricks, their capillary and mechanical properties, salinity analysis and microbiological analyses of materials. The undeniable value of the conducted research is a detailed diagnosis of historical building materials, which is a significant contribution to the knowledge of old construction techniques.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 59-69
Keywords: architektura; medieval architecture; building materials; material testing; architectural conservation; architektura średniowieczna; materiały budowlane; badanie materiałów; konserwacja architektury